Hemoglobin modulation affects physiology and patient reported outcomes in anemic and non-anemic subjects: An umbrella review - Tonino, R. P. B.; Zwaginga, L. M.; Schipperus, M. R.; Zwaginga, J. J. (Frontiers in Physiology, 2023)
Background: An abnormal hemoglobin concentration has a substantial effect on a person’s quality of life and physiology. Lack of tools that effectively evaluate hemoglobin-related outcomes leads to uncertainty regarding optimal hemoglobin levels, transfusion thresholds and treatment targets. We therefore aim to summarize reviews that assess the effects of hemoglobin modulation on the human physiology at various baseline hemoglobin levels, and identify gaps in existing evidence. Methods: We conducted an umbrella review of systematic reviews. PubMed, MEDLINE (OVID), Embase, Web of Science, Cochrane Library and Emcare were searched from inception to the 15th of April 2022 for studies that reported on physiological and patient reported outcomes following a hemoglobin change. Results: Thirty-three reviews were included of which 7 were scored as of high quality and 24 of critically low quality using the AMSTAR-2 tool. The reported data generally show that an increase in hemoglobin leads to improvement of patient reported and physical outcomes in anaemic and non-anaemic subjects. At lower hemoglobin levels, the effect of a hemoglobin modulation on quality of life measures appears more pronounced. Conclusion: This overview has revealed many knowledge gaps due to a lack of high-quality evidence. For chronic kidney disease patients, a clinically relevant benefit of increasing the hemoglobin levels up until 12 g/dL was found. However, a personalized approach remains necessary due to the many patient-specific factors that affect outcomes. We strongly encourage future trials to incorporate physiological outcomes as objective parameters together with subjective, but still very important, patient reported outcome measures.